Dynamic Performance Evaluation of an Integrated 15 MW Floating Offshore Wind Turbine Under Typhoon and ECD Conditions - Liu, Shiqi; Chuang, Zhenju; Qu, Yan; Li, Xin; Li, Chunzheng; He, Zhen (Frontiers in Energy Research, 2022)
Technology innovation has led to an increase in floating wind turbine size aimed at releasing the pressure on capital cost and increasing its capacity factor. Large-size turbines pose high challenges regarding design with essential structure reliability. The dynamic performance of an integrated 15-megawatt (MW) wind turbine under extreme sea loads is investigated in this paper. Platform motions, mooring system positioning forces, sizeable blades, and tower behaviors are all studied under the targeted typhoon condition and extreme coherent gust with direction change (ECD) wind condition. Potential flow theory is used to analyze the first-order wave load, mean-drift wave load, and second-order difference-frequency wave load on the substructure of the ultra-large 15 MW floating offshore wind turbine (FOWT). The blade element momentum (BEM) theory is adopted for the calculation of the aerodynamic loads on the floating wind turbine, and the finite element method (FEM) is applied to analyze the mooring lines of the floating wind turbine. The results show that the effect of quadratic transfer function (QTF) will significantly increase the dynamic response of FOWT under the typhoon sea state. The ECD wind condition has an influential impact on the motion responses, the axial force of the mooring lines, and structural responses under the normal operating state.